2019
DOI: 10.1021/acs.chemrev.9b00079
|View full text |Cite
|
Sign up to set email alerts
|

Palladium/Norbornene Cooperative Catalysis

Abstract: Palladium/norbornene cooperative catalysis has emerged as a distinct approach to construct polyfunctionalized arenes from readily available starting materials. This Review provides a comprehensive overview of this field, including the early stoichiometric investigations, catalytic reaction developments, as well as the applications in the syntheses of bioactive compounds and polymers. The section of catalytic reactions is divided into two parts according to the reaction initiation mode: Pd(0)-initiated reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
160
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(165 citation statements)
references
References 361 publications
(633 reference statements)
1
160
0
4
Order By: Relevance
“…[1,2] To design and synthesize structurally new PAHs as candidates of organic materials, reactions that allow atomically precise synthesis of PAHs are in high demand. [3] In the course of our research on the development of annulation reactions by CÀH functionalization, [4] we envisioned that twofold inter-and intramolecular C À H activation of "bay"-halogenated phenylenes would provide a streamlined synthesis of p-extended PAHs (Figure 1 a). In 2018, we reported a palladium-catalyzed annulative chlorophenylene dimerization, which gave triphenylenecored partially fused PAHs.…”
mentioning
confidence: 99%
“…[1,2] To design and synthesize structurally new PAHs as candidates of organic materials, reactions that allow atomically precise synthesis of PAHs are in high demand. [3] In the course of our research on the development of annulation reactions by CÀH functionalization, [4] we envisioned that twofold inter-and intramolecular C À H activation of "bay"-halogenated phenylenes would provide a streamlined synthesis of p-extended PAHs (Figure 1 a). In 2018, we reported a palladium-catalyzed annulative chlorophenylene dimerization, which gave triphenylenecored partially fused PAHs.…”
mentioning
confidence: 99%
“…Communications to the formation of spirocyclic product 6 in 63 %y ield (Scheme 3a). Based on literature precedents, [5][6][7][8][9]13] this outcome implies that the reaction proceeds via cyclopalladation to form the key intermediate II,f ollowed by intermolecular biaryl coupling involving Pd IV -species III,with termination by dearomative spiroannulation of IV.T he assumed mechanism was further supported by the reaction performance between 1aand 7 (Scheme 3b). Theoutcome of this reaction indicated that:1)Pd IV species III' ',which is like III,was involved as the intermediate;2 )reductive elimination of III' ' and the subsequent C À Harylation took place via two pathways.Moreover, at hree-component control reaction (Scheme 3c)r evealed that an alkyne tethered on the aryl iodide partner was crucial for the intermolecular cross-coupling of such two different aryl halides.…”
Section: Angewandte Chemiementioning
confidence: 81%
“…[5] In particular, the use of ar igid and strained olefin norbornene (NBE) in Pdcatalysis,n amely the Catellani reaction, has become av ery useful method for the direct construction of am yriad of unsymmetrical biaryls. [6] Thee lectron-rich palladacycle A, which was formed in situ through NBE-assisted ortho-CÀH palladation, was prone to couple with asecond aryl iodide.So the early examples were achieved using two molecules of the same aryl iodide, [7] while attempts with different aryl iodides led to poor selectivity. [8] To enable more difficult crosscouplings for making as eries of unsymmetrical biaryl-based polycyclic scaffolds,f ine tuning was required for both partners,byemploying aryl iodides with an electron-donating ortho substituent and aryl halides (Cl or Br) with an electronwithdrawing or ortho chelating group (Scheme 1a).…”
mentioning
confidence: 99%
“…[1d] Herein, we report the first use of ac arboxy directing group (DG) for remote selective CÀHactivation of hydrocinnamic acid derivatives and related arenes,with aPd catalyst, at the meta-position (Scheme 1c). [7][8][9] Thegenerality of this approach was demonstrated by its compatibility with both Pd/Pd 0 and Pd II /Pd IV (or Pd II /Pd III )catalytic processes to achieve meta-C À Ho lefination and arylation of av ariety of molecular structures. [10,11] Notably,d irect remote meta-C À H arylation of hydrocinnamic acids using low-cost aryl iodides was not previously successful when using the auxiliaryassisted CÀHa ctivation strategy.…”
mentioning
confidence: 99%
“…First, oxidant re-evaluation demonstrated that both AgOAc and Ag 2 CO 3 were viable oxidants but they would result in minor decarboxylation of the carboxy DG in the olefinated products;AgOPiv did not lead to decarboxylation and was therefore the optimal oxidant (Table 1, entries [5][6][7][8].…”
mentioning
confidence: 99%